Kiai Abdul Hamid Pasuruan dan Kontribusinya untuk Moderasi Islam - Wasid, Wasid; Mahsun, Mahsun (AL-FIKRAH: Jurnal Studi Ilmu Pendidikan dan Keislaman, 2018)
Kiai Abdul Hamid Pasuruan is a phenomenal figure, even known by his conscience by layers ofsociety. He has inherited many things related to the earthing of islamic values, especially in teachingislamic academic theory of Ahl Sunna wal al-jamaah. His legacies both of –his thought and his attitudefor facing this life—that can be able to appease for people, up to now many people come to visit hisgrave for pilgrimaging destination. By him, Islam is served softly without fears to others.. Moreover,He was forwarding the happiness of others people, before his self was happy. This step is done basedon his holistic understanding of islam, which is said that able to combine the logic of normative fiqhwith substantial values sufism in the context of life and the large community. The combination ofnormativeity and sufism were ushering firmly and softly. It means, friendly in building therelationship with people. within the sphere of life practice.Kiai Hamid was able to invite people fordoing the obligation of islam, while in the context of persuading and giving example for them, theimportance is creating of maintaining harmony each others.